2020
DOI: 10.1155/2020/9435972
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Serum Concentrations of Selenium, Copper, and Zinc during Pregnancy Are Associated with Risk of Spontaneous Preterm Birth: A Case-Control Study from Malawi

Abstract: Preterm birth is delivery before 37 completed weeks. A study was conducted to evaluate the association of maternal serum concentrations of selenium, copper, and zinc and preterm birth. There were 181 women in this nested case-control study, 90/181 (49.7%) term and 91/181 (50.3%) preterm pregnant women. The overall mean serum concentration of selenium was 77.0, SD 19.4 μg/L; of copper was 2.50, SD 0.52 mg/L; and of zinc was 0.77, SD 0.20 mg/L with reference values of 47-142 μg/L, 0.76-1.59 mg/L, and 0.59-1.11 m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 45 publications
3
25
0
Order By: Relevance
“…A nested case-control investigation recently conducted in Malawi included 181 women, 90/181 (49.7%) term and 91/181 (50.3%) preterm pregnant women [57]. Se levels were analyzed together with Zn and Cu.…”
Section: Se and Impact On Preterm Birthmentioning
confidence: 99%
“…A nested case-control investigation recently conducted in Malawi included 181 women, 90/181 (49.7%) term and 91/181 (50.3%) preterm pregnant women [57]. Se levels were analyzed together with Zn and Cu.…”
Section: Se and Impact On Preterm Birthmentioning
confidence: 99%
“…Osendarp et al 109 also suggested that maternal zinc supplementation has beneficial effect on neonatal immune status, early neonatal morbidity and infant infections. Contrary to the findings of other studies, Chiudzu et al 110 demonstrated elevated concentrations of serum copper and zinc in Malawian women giving preterm birth. Favier et al 56 also reported beneficial effects of zinc supplementation on male sterility and in reducing complications during pregnancy.…”
Section: Zinc Supplementation and Preterm Birthmentioning
confidence: 60%
“…A study performed in Australia found that an excessive dietary intake of Se was associated with prolonged pregnancy. In contrast, Se levels in Japanese pregnant women were not related to pre-term births [53,54]. These findings indicate the need to investigate the effect of supplementary intake of Se not only in pregnant women, but also in the general population.…”
Section: Discussionmentioning
confidence: 78%